TEKNIK BRAINSTORMING DALAM LAYANAN KONSELING KELOMPOK TERHADAP KOMUNIKASI INTERPERSONAL SISWA SMK NEGERI 2 CIMAHI - Novela Widya Saphira; Asep Samsudin; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to describe the implementation of treatment, response and constraints of group counseling services with brainstorming techniques on students' interpersonal communication. This study uses descriptive qualitative research methods. The subjects in this study were students of class X SMKN 2 Cimahi. namely 3 students. Data analysis techniques used are collection, reduction, presentation and conclusion of data. The results obtained in the study, namely the brainstorming technique in group counseling services are an effort made by BK teachers as assistance to students who have low interpersonal communication, the services carried out are divided into 3 stages, namely the formation stage, the activity stage and the termination stage. Keywords: : Group Counseling, Brainstorming Techniques, Interpersonal Communication